Low-sodium high-wear-resistance white corundum and preparation process thereof
By adopting low-sodium high-wear-resistant white corundum composite powder, combined with modified glass fiber and heat-resistant modifier, the problems of abrasive particles crushing and poor resin heat resistance during the cutting process of white corundum grinding wheel are solved, and the effect of improving the working efficiency and service life of the grinding wheel is achieved.
Patent Information
- Application Number
- CN202510004613.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-01-02
AI Technical Summary
During the cutting process, the abrasive particles are broken due to insufficient toughness, which affects the working efficiency and processing quality. At the same time, the combination between the white corundum and the resin is poor, and the resin has poor heat resistance, which affects the service life of the grinding wheel.
Low-sodium high wear-resistant white corundum composite powder, including low-sodium white corundum original powder, phenolic resin powder, modified glass fiber, heat-resistant modifier and potassium ice crystal, are used to improve the binding of white corundum with resin and the heat resistance of resin through the preparation method and preparation process of modified glass fiber.
It effectively improves the working efficiency and service life of the white corundum grinding wheel. Through the synergy between modified glass fiber and heat-resistant modifier, the heat resistance of the resin and the overall performance of the grinding wheel are improved.
Smart Images

Figure CN119683904A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of white corundum composite powder, and particularly relates to low-sodium and highly wear-resistant white corundum and a preparation process thereof. Background Art
[0002] White corundum is the main raw material for grinding wheels. White corundum grinding wheels are widely used in various industrial processes due to their high hardness and good grinding performance. However, due to the insufficient toughness of white corundum, it will cause the abrasive particles to break during the cutting process, affecting work efficiency and processing quality. In order to address this shortcoming, resin is added as a binder when making composite white corundum powder. The resin binder has good elasticity and toughness, which can improve the impact resistance of white corundum grinding wheels to a certain extent, making white corundum grinding wheels perform well in high-speed grinding and heavy-load grinding.
[0003] However, since white corundum itself is easy to agglomerate, white corundum and resin cannot be well combined, and the resin has poor heat resistance and may soften or decompose at high temperatures, affecting the working efficiency and service life of the grinding wheel. Summary of the invention
[0004] In order to solve the problems existing in the background technology, the present invention provides a low-sodium and high-wear-resistant white corundum and a preparation process, which ensures that when the low-sodium and high-wear-resistant white corundum is used to prepare a white corundum grinding wheel, the working efficiency and service life of the prepared white corundum grinding wheel can be effectively improved.
[0005] In order to achieve the above-mentioned purpose, in a first aspect, the present invention provides a low-sodium and highly wear-resistant white corundum, which comprises the following components, calculated by weight: 68-72 parts of low-sodium white corundum raw powder, 8-11 parts of phenolic resin powder, 4-7 parts of modified glass fiber, 3-5 parts of heat-resistant modifier and 4-6 parts of potassium cryolite.
[0006] Furthermore, the preparation method of the modified glass fiber is as follows: A1. Clean the glass fiber in a cleaning apparatus to obtain clean glass fiber; A2, completely immersing the clean glass fiber obtained in A1 in a concentrated nitric acid solution, and placing the concentrated nitric acid solution containing the clean glass fiber in a constant temperature box for constant temperature treatment to obtain an acidified glass fiber; A3. Wash the acidified glass fiber obtained in A2 with deionized water and dry it in a drying oven under vacuum to obtain modified glass fiber.
[0007] Furthermore, in A1, the glass fiber is cleaned in a KQ-100DE ultrasonic cleaner using deionized water, anhydrous ethanol, and deionized water in sequence, and each cleaning time is 8-12 minutes.
[0008] Furthermore, in A2, the mass fraction of the concentrated nitric acid solution is 62%-68%, and the mass ratio of the clean glass fiber to the concentrated nitric acid solution is 1:(40-50).
[0009] Furthermore, in A2, the temperature of the constant temperature treatment is 75-80°C, and the time of the constant temperature treatment is 2.5-3h.
[0010] Furthermore, in A3, the vacuum drying temperature is 57-62° C., and the vacuum drying time is 10-11 h.
[0011] Furthermore, the heat-resistant modifier is MS-NB.
[0012] Furthermore, the low-sodium and highly wear-resistant white corundum is used to prepare white corundum grinding wheels.
[0013] In a second aspect, the present invention provides a preparation process of the above-mentioned low-sodium and highly wear-resistant white corundum, comprising the following steps: S1, adding low sodium white corundum raw powder, phenolic resin powder and potassium cryolite into a mixer, mixing to obtain a first mixture; S2, adding a heat-resistant modifier and modified glass fiber to the first mixture obtained in S1, mixing evenly, to obtain a second mixture, namely the low-sodium and highly wear-resistant white corundum.
[0014] Furthermore, in S1, the mixing time is 30-35 min; in S2, the mixing time is 55-60 min.
[0015] This application has the following beneficial effects: 1. The addition of the modified fiber of the present invention, on the one hand, forms a stronger interface bond with the low sodium white corundum raw powder particles, acts as a bridge, reduces the direct contact between the low sodium white corundum raw powder particles, reduces the agglomeration phenomenon, promotes the uniform distribution of the low sodium white corundum raw powder particles, and effectively improves the dispersion state of the low sodium white corundum raw powder particles in the matrix.
[0016] On the other hand, the modified fiber itself has a high melting point and strong heat resistance, and it can form a thermal barrier between resins to prevent the rapid transfer of heat from the working end of the grinding wheel, thereby protecting the resin from the influence of high temperature to a certain extent. At the same time, the modified glass fiber can act as a skeleton in the resin, limiting the movement of the resin molecular chain at high temperature and improving the thermal stability of the resin at high temperature.
[0017] In this way, the two effects work together to effectively improve the working efficiency and service life of the white corundum grinding wheel.
[0018] 2. The modified glass fiber of the present invention is used together with a heat-resistant modifier. On the one hand, they restrict the movement of the resin molecular chain through different mechanisms, and at the same time, inhibit the degradation process of the resin at high temperature, thereby synergistically improving the heat resistance of the resin.
[0019] On the other hand, the surface of modified glass fiber is much more active than its internal structure, and can produce a strong adsorption effect on both the resin and the heat-resistant modifier, so that the heat-resistant modifier can act on the resin more specifically and improve the heat resistance of the resin. It also weakens the effect of the heat-resistant modifier on the fluidity of the grinding wheel material, avoids the grinding wheel surface from being excessively dense and smooth, and avoids further reduction in the heat dissipation capacity of the grinding wheel.
[0020] In this way, the modified glass fiber and the heat-resistant modifier work synergistically to not only jointly improve the heat resistance of the grinding wheel, but also effectively prevent the heat dissipation performance of the grinding wheel from further decreasing due to the addition of the heat-resistant modifier, thereby synergistically improving the working efficiency and service life of the grinding wheel. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 , a comparative trend chart of the working efficiency test data of the white corundum grinding wheel cutting discs obtained in Examples 1 to 5 and Comparative Examples 1 to 5 in the test examples of the present invention; Figure 2 , a comparative trend chart of the service life test data of the white corundum grinding wheel cutting discs obtained in Examples 1 to 5 and Comparative Examples 1 to 5 in the test examples of the present invention. DETAILED DESCRIPTION
[0022] The present application is further described in detail below with reference to the embodiments.
[0023] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0024] Example 1: (1) Modified glass fiber is prepared by the following method: A1. Clean the glass fiber in a KQ-100DE ultrasonic cleaner using deionized water, anhydrous ethanol, and deionized water in sequence, with each cleaning time being 10 minutes to obtain a clean glass fiber.
[0025] A2. Completely immerse the clean glass fiber obtained in A1 in a concentrated nitric acid solution. The mass fraction of the concentrated nitric acid solution is 65%. The mass ratio of the clean glass fiber to the concentrated nitric acid solution is 1:45. Place the concentrated nitric acid solution containing the clean glass fiber in a constant temperature box for constant temperature treatment. The temperature of the constant temperature treatment is 78°C and the time of the constant temperature treatment is 2.8 hours. Then filter to obtain the acidified glass fiber.
[0026] A3. Wash the acidified glass fiber obtained in A2 with deionized water, and vacuum dry it in a drying oven at a vacuum drying temperature of 60°C for 10.5 h to obtain modified glass fiber.
[0027] Among them, the glass fiber is chopped glass fiber (BX-139), grade A, 3-4.5mm, purchased from Taian Senyang Composite Materials Co., Ltd.
[0028] (2) A preparation process of low-sodium and highly wear-resistant white corundum, comprising the following steps: S1. Add 70 parts of low-sodium white corundum powder, 9 parts of phenolic resin powder and 5 parts of potassium cryolite into a mixer by weight, and mix them at a mixing speed of 220 r / min for 32 min to obtain a first mixture.
[0029] S2. According to the same standard weight proportions, add 4 parts of heat-resistant modifier and 6 parts of modified glass fiber to the first mixture obtained in S1, continue mixing, and keep the mixing speed at 220r / min for 57min to obtain the second mixture, which is low-sodium and highly wear-resistant white corundum.
[0030] Among them, the raw powder of low sodium white corundum is 100 mesh. Phenolic resin powder (grade 2123) is purchased from Jinan Dahui Chemical Technology Co., Ltd. Potassium cryolite (100 mesh) is purchased from Zhengzhou Tianzhirui New Materials Co., Ltd. The heat-resistant modifier is MS-NB (branded by Japan Electric Chemical), purchased from Borida New Materials Co., Ltd.
[0031] The low sodium and high wear-resistant white corundum is used to prepare white corundum grinding wheels. The specific preparation method is as follows: according to the same standard weight, add 3 parts of liquid phenolic resin to the low sodium and high wear-resistant white corundum, put it in a mold and scrape it flat, cover the upper template and push it into the press under 18MPa pressure for 5s, release the pressure and take it out of the mold to obtain the molded blank. Put the molded blank into the hardening furnace for hardening, start the temperature at 60℃, and increase the hardening temperature from 60℃ to the highest hardening temperature of 185℃ after 10h, and then maintain the highest hardening temperature for 8h. After the hardening treatment is completed, slowly cool it to room temperature, and after unloading the sheet, a white corundum grinding wheel cutting sheet with a specification of 400*3.2*32 is obtained.
[0032] Example 2: The difference between this example and Example 1 is that: (1) the modified glass fiber is prepared, and the preparation method thereof is as follows: A1. Clean the glass fiber in a KQ-100DE ultrasonic cleaner using deionized water, anhydrous ethanol, and deionized water in sequence, with each cleaning time being 8 minutes to obtain a clean glass fiber.
[0033] A2. Completely immerse the clean glass fiber obtained in A1 in a concentrated nitric acid solution. The mass fraction of the concentrated nitric acid solution is 62%. The mass ratio of the clean glass fiber to the concentrated nitric acid solution is 1:40. Place the concentrated nitric acid solution containing the clean glass fiber in a constant temperature box for constant temperature treatment. The temperature of the constant temperature treatment is 75°C and the time of the constant temperature treatment is 2.5 hours. Then filter to obtain the acidified glass fiber.
[0034] A3. Wash the acidified glass fiber obtained in A2 with deionized water, and vacuum dry it in a drying oven at a vacuum drying temperature of 57°C for 10 h to obtain modified glass fiber.
[0035] Example 3: The difference between this example and Example 1 is that: (1) the modified glass fiber is prepared, and the preparation method thereof is as follows: A1. Clean the glass fiber in a KQ-100DE ultrasonic cleaner using deionized water, anhydrous ethanol, and deionized water in sequence, with each cleaning time being 12 minutes to obtain a clean glass fiber.
[0036] A2. Completely immerse the clean glass fiber obtained in A1 in a concentrated nitric acid solution, wherein the mass fraction of the concentrated nitric acid solution is 68% and the mass ratio of the clean glass fiber to the concentrated nitric acid solution is 1:50. Place the concentrated nitric acid solution containing the clean glass fiber in a constant temperature box for constant temperature treatment at a temperature of 80°C for 3 hours, and then filter to obtain the acidified glass fiber.
[0037] A3. Wash the acidified glass fiber obtained in A2 with deionized water, and vacuum dry it in a drying oven at a vacuum drying temperature of 62°C for 11 hours to obtain modified glass fiber.
[0038] Example 4: The difference between this example and Example 1 is that: (2) A preparation process of low-sodium and highly wear-resistant white corundum comprises the following steps: S1. Add 68 parts of low-sodium white corundum powder, 8 parts of phenolic resin powder and 4 parts of potassium cryolite into a mixer by weight, and mix them at a mixing speed of 220 r / min for 30 min to obtain a first mixture.
[0039] S2. According to the same standard weight proportions, add 3 parts of heat-resistant modifier and 4 parts of modified glass fiber to the first mixture obtained in S1, continue mixing, and keep the mixing speed at 220r / min for 55min to obtain the second mixture, which is low-sodium and highly wear-resistant white corundum.
[0040] Example 5: The difference between this example and Example 1 is that: (2) A preparation process of low-sodium and highly wear-resistant white corundum comprises the following steps: S1. Add 72 parts of low-sodium white corundum powder, 11 parts of phenolic resin powder and 6 parts of potassium cryolite into a mixer by weight, and mix them at a mixing speed of 220 r / min for 35 min to obtain a first mixture.
[0041] S2. According to the same standard weight proportions, add 5 parts of heat-resistant modifier and 7 parts of modified glass fiber to the first mixture obtained in S1, continue mixing, and keep the mixing speed at 220r / min for 60min to obtain the second mixture, which is low-sodium and highly wear-resistant white corundum.
[0042] Comparative Example 1: The difference between this comparative example and Example 1 is that the modified glass fiber and the heat-resistant modifier are deleted.
[0043] Specifically, a preparation process of low-sodium and highly wear-resistant white corundum comprises the following steps: S1. Add 70 parts of low-sodium white corundum powder, 9 parts of phenolic resin powder and 5 parts of potassium cryolite into a mixer by weight, and mix them at a mixing speed of 220 r / min for 32 min to obtain a first mixture.
[0044] S2. Continue to mix the first mixture obtained in S1, the mixing speed is still maintained at 220r / min, the mixing time is 57min, and the second mixture is obtained, that is, low-sodium and highly wear-resistant white corundum.
[0045] Comparative Example 2: The difference between this comparative example and Example 1 is that the modified glass fiber is deleted.
[0046] Specifically, a preparation process of low-sodium and highly wear-resistant white corundum comprises the following steps: S1. Add 70 parts of low-sodium white corundum powder, 9 parts of phenolic resin powder and 5 parts of potassium cryolite into a mixer by weight, and mix them at a mixing speed of 220 r / min for 32 min to obtain a first mixture.
[0047] S2. According to the same standard weight proportion, 4 parts of heat-resistant modifier are added to the first mixture obtained in S1, and the mixing is continued. The mixing speed is still maintained at 220r / min, and the mixing time is 57min to obtain the second mixture, which is low-sodium and highly wear-resistant white corundum.
[0048] Comparative Example 3: This comparative example differs from Example 1 in that the heat-resistant modifier is deleted and the modified glass fiber is replaced by glass fiber.
[0049] Specifically, a preparation process of low-sodium and highly wear-resistant white corundum comprises the following steps: S1. Add 70 parts of low-sodium white corundum powder, 9 parts of phenolic resin powder and 5 parts of potassium cryolite into a mixer by weight, and mix them at a mixing speed of 220 r / min for 32 min to obtain a first mixture.
[0050] S2. According to the same standard weight proportions, add 6 parts of glass fiber to the first mixture obtained in S1, continue mixing, and keep the mixing speed at 220r / min for 57min to obtain the second mixture, which is low-sodium and highly wear-resistant white corundum.
[0051] Comparative Example 4: The difference between this comparative example and Example 1 is that the modified glass fiber is replaced by glass fiber.
[0052] Specifically, a preparation process of low-sodium and highly wear-resistant white corundum comprises the following steps: S1. Add 70 parts of low-sodium white corundum powder, 9 parts of phenolic resin powder and 5 parts of potassium cryolite into a mixer by weight, and mix them at a mixing speed of 220 r / min for 32 min to obtain a first mixture.
[0053] S2. According to the same standard weight proportions, add 4 parts of heat-resistant modifier and 6 parts of glass fiber to the first mixture obtained in S1, continue mixing, and keep the mixing speed at 220r / min for 57min to obtain the second mixture, which is low-sodium and highly wear-resistant white corundum.
[0054] Comparative Example 5: The difference between this comparative example and Example 1 is that the heat-resistant modifier is deleted.
[0055] Specifically, a preparation process of low-sodium and highly wear-resistant white corundum comprises the following steps: S1. Add 70 parts of low-sodium white corundum powder, 9 parts of phenolic resin powder and 5 parts of potassium cryolite into a mixer by weight, and mix them at a mixing speed of 220 r / min for 32 min to obtain a first mixture.
[0056] S2. According to the same standard weight proportions, add 6 parts of modified glass fiber to the first mixture obtained in S1, continue mixing, and keep the mixing speed at 220r / min for 57min to obtain the second mixture, which is low-sodium and highly wear-resistant white corundum.
[0057] Test example: Test object: White corundum grinding wheel cutting discs were prepared from Example 1 to Example 5 and Comparative Example 1 to Comparative Example 5.
[0058] Test items: ①Work efficiency; ②Service life.
[0059] Test method: Each test object (white corundum grinding wheel cutting disc) is mounted on a high-speed cutting machine, with a rotation speed of 2800r / min, a cutting pressure of 16.46N, and a cutting workpiece of 8# (80*43*5) hot-rolled channel steel, made of Q235. Work efficiency = cut metal mass g / cutting time s, the larger the value, the higher the work efficiency; service life = cut metal mass g / resin grinding wheel loss mass g, the larger the value, the longer the service life.
[0060] Test results: See Table 1.
[0061] Result analysis: Analyze Example 1-Example 5 and combine the data in Table 1 and Figure 1-Figure 2 It can be seen that the working efficiency test data of the white corundum grinding wheel cutting disc prepared by the low-sodium and high-wear-resistant white corundum prepared in the present invention (Example 1-Example 5) is as high as 2.57 (g / s) or more, and the service life test data is as high as 3.61 (g / g) or more. This shows that when the low-sodium and high-wear-resistant white corundum prepared in the present invention is used to prepare a white corundum grinding wheel, the working efficiency and service life of the prepared white corundum grinding wheel can be effectively improved.
[0062] Analyze Example 1 and Comparative Examples 1-5 and combine the data in Table 1 and Figure 1-Figure 2 By comparing Comparative Example 1 with Comparative Example 2, it can be seen that compared with Comparative Example 1, a heat-resistant modifier is added to the raw material components of Comparative Example 2. As a result, the working efficiency test data of the white corundum grinding wheel obtained in Comparative Example 2 is 1.98 (g / s), which is significantly less than 2.17 (g / s) of Comparative Example 1; and the service life test data of the white corundum grinding wheel obtained in Comparative Example 2 is 2.71 (g / g), which is also significantly less than 3.04 (g / g) of Comparative Example 1. This shows that the increase of the heat-resistant modifier in the raw material components alone will cause the working efficiency and service life of the white corundum grinding wheel finally obtained to decrease instead of increase.
[0063] This is because the heat-resistant modifier MS-NB, in addition to improving the heat resistance of the grinding wheel, also contains active maleic anhydride groups, which can act as a compatibilizer to promote uniform mixing between different materials, reduce phase separation, and change the fluidity of the grinding wheel material, which helps the material to better fill the tiny pores on the surface of the mold or grinding wheel during the molding process, thereby forming a denser and smoother surface. When the surface of the grinding wheel is denser and smoother, the contact area between the surface and the air is reduced, thereby reducing the convective heat transfer efficiency and causing the heat dissipation capacity of the grinding wheel to decrease. The grinding wheel generates a lot of heat during operation. If this heat cannot be dissipated in time, it will accumulate inside the grinding wheel, which will not only affect the cutting performance of the grinding wheel, but also accelerate the wear and aging of the grinding wheel, thereby reducing the working efficiency and service life of the grinding wheel.
[0064] By comparing Comparative Example 1 and Comparative Example 3, it can be seen that compared with Comparative Example 1, glass fiber is added to the raw material components of Comparative Example 3, and the working efficiency test data of the white corundum grinding wheel prepared in Comparative Example 3 is 2.23 (g / s), slightly greater than 2.17 (g / s) of Comparative Example 1; and the service life test data of the white corundum grinding wheel prepared in Comparative Example 3 is 3.12 (g / g), also slightly greater than 3.04 (g / g) of Comparative Example 1. It shows that the addition of glass fiber alone in the raw material components can improve the working efficiency and service life of the white corundum grinding wheel finally prepared.
[0065] By comparing Comparative Example 3 with Comparative Example 4, it can be seen that compared with Comparative Example 3, a heat-resistant modifier is added to the raw material components of Comparative Example 4, and the working efficiency test data of the white corundum grinding wheel prepared in Comparative Example 4 is 2.11 (g / s), which is less than 2.23 (g / s) of Comparative Example 3; and the service life test data of the white corundum grinding wheel prepared in Comparative Example 4 is 2.93 (g / g), which is also less than 3.12 (g / g) of Comparative Example 3. This shows that when glass fiber exists in the raw material components, adding a heat-resistant modifier will still lead to a decrease in the working efficiency and service life of the white corundum grinding wheel finally prepared.
[0066] By comparing Comparative Example 3 with Comparative Example 5, it can be seen that compared with Comparative Example 3, the glass fiber in the raw material component of Comparative Example 5 is replaced by the modified glass fiber of the present invention, and the working efficiency test data of the white corundum grinding wheel prepared in Comparative Example 5 is 2.48 (g / s), which is greater than 2.23 (g / s) of Comparative Example 3; and the service life test data of the white corundum grinding wheel prepared in Comparative Example 5 is 3.43 (g / g), which is also greater than 3.12 (g / g) of Comparative Example 3. This shows that replacing the glass fiber in the raw material component with the modified glass fiber of the present invention can further improve the working efficiency and service life of the white corundum grinding wheel finally prepared.
[0067] By comparing Comparative Example 5 with Example 1, it can be seen that compared with Comparative Example 5, a heat-resistant modifier is added to the raw material components of Example 1, and the working efficiency test data of the white corundum grinding wheel prepared in Example 1 is 2.61 (g / s), which is greater than 2.48 (g / s) of Comparative Example 5; and the service life test data of the white corundum grinding wheel prepared in Example 1 is 3.66 (g / g), which is also greater than 3.43 (g / g) of Comparative Example 5. This shows that when modified glass fiber exists in the raw material components, the addition of a heat-resistant modifier can produce a synergistic effect, thereby synergistically improving the working efficiency and service life of the white corundum grinding wheel finally prepared.
[0068] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0069] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A low sodium and highly wear-resistant white corundum, characterized in that: The invention comprises the following components by weight: 68-72 parts of low-sodium white corundum raw powder, 8-11 parts of phenolic resin powder, 4-7 parts of modified glass fiber, 3-5 parts of heat-resistant modifier and 4-6 parts of potassium cryolite.
2. The low sodium and highly wear-resistant white corundum according to claim 1, characterized in that: The preparation method of the modified glass fiber is as follows: A1. Clean the glass fiber in a cleaning apparatus to obtain clean glass fiber; A2, completely immersing the clean glass fiber obtained in A1 in a concentrated nitric acid solution, and placing the concentrated nitric acid solution containing the clean glass fiber in a constant temperature box for constant temperature treatment to obtain an acidified glass fiber; A3. Wash the acidified glass fiber obtained in A2 with deionized water and dry it in a drying oven under vacuum to obtain modified glass fiber.
3. The low sodium and highly wear-resistant white corundum according to claim 2, characterized in that: In A1, the glass fiber is cleaned in a KQ-100DE ultrasonic cleaner using deionized water, anhydrous ethanol, and deionized water in sequence, and each cleaning time is 8-12 minutes.
4. The low sodium and highly wear-resistant white corundum according to claim 2, characterized in that: In A2, the mass fraction of the concentrated nitric acid solution is 62%-68%, and the mass ratio of the clean glass fiber to the concentrated nitric acid solution is 1:(40-50).
5. The low sodium and high wear-resistant white corundum according to claim 2, characterized in that: In A2, the temperature of the constant temperature treatment is 75-80°C, and the time of the constant temperature treatment is 2.5-3h.
6. The low sodium and high wear-resistant white corundum according to claim 2, characterized in that: In A3, the vacuum drying temperature is 57-62°C, and the vacuum drying time is 10-11h.
7. The low sodium and highly wear-resistant white corundum according to claim 1, characterized in that: The heat-resistant modifier is MS-NB.
8. The low sodium and high wear-resistant white corundum according to claim 1, characterized in that: The low-sodium and highly wear-resistant white corundum is used for preparing white corundum grinding wheels.
9. A process for preparing low sodium and highly wear-resistant white corundum according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, adding low sodium white corundum raw powder, phenolic resin powder and potassium cryolite into a mixer, mixing to obtain a first mixture; S2, adding a heat-resistant modifier and modified glass fiber to the first mixture obtained in S1, mixing evenly, to obtain a second mixture, namely the low-sodium and highly wear-resistant white corundum.
10. The preparation process of low sodium and high wear-resistant white corundum according to claim 9, characterized in that: In S1, the mixing time is 30-35 min; in S2, the mixing time is 55-60 min.
Citation Information
Patent Citations
Multi-functional fiber reinforced resin cutting grinding wheel and manufacture technology thereof
CN110000717A
High-temperature-resistant nylon engineering plastic and preparation method thereof
CN119081395A
Grinding wheels
GB2028860A
Abrasive composition and articles incorporating same
US5273558A